ANAEROBIC BIODEGRADATION OF SULPHATE EMPLOYING ANIMAL MANURE AS A COST EFFECTIVE GROWTH SUBSTRATE - A. Hussain; H. A. Shakir; J. I. Qazi (Journal of Animal and Plant Sciences, 2014)
The toxicity of various compound forms of sulphates to animals is well known. Therefore, the sulphate rich industrial wastewaters must be treated before discharging them to the environment. In this context, the present study reports the implication and assessment of two different states of bovine and poultry manures as sources of carbon and energy in the treatment of artificially prepared sulphate rich wastewater while recruiting pure cultures of Desulfovibrio desulfuricans-HAQ3. About 73% sulphate reduction was achieved in a 60 days trial of anaerobic incubation when composted bovine manure was used as an electron donor. Sulphate reduction efficiency remained limited to 27%, 31% and 36% for fresh bovine manure, poultry manure and poultry litter as electron donors, respectively. The findings of this study will be very helpful in developing economical and environmental friendly bioremediation process(es) addressing the sulphate pollution.
Keywords: Economical bioremediation; Electron donor; SRB; Bovine manure; Poultry manure; Poultry litter